Human aspects in software architecture decision making: a literature review - Tang, Antony; Paech, Barbara; Hesse, Tom-Michael (ICSA 2017, 2017)
Despite past efforts, we have little understanding and limited research efforts on how architects make decisions in the real-world settings. It seems that software architecture researchers make implicit assumption that decision making by software architects can be a rational and prescribed process. Such an assumption is disputed in other fields such as economics and decision research. This paper studies the current state of software architecture decision making research in terms of human behaviors and practice. We carried out a literature review on software architecture decision making. We classified papers into decision making behavior and decision making practice and identified the research relationships between them. We found that decision making is a mental activity. Research into the behavioral aspects of software architecture decision making for incorporation into architectural design practices is required. We suggest three research topics on human aspects to improve software architecture practices.